About cookies on this site Our websites require some cookies to function properly (required). In addition, other cookies may be used with your consent to analyze site usage, improve the user experience and for advertising. For more information, please review your options. By visiting our website, you agree to our processing of information as described in IBM’sprivacy statement. To provide a smooth navigation, your cookie preferences will be shared across the IBM web domains listed here.
August 2007
<<July August September>>
Ponder This Solution:
The sequence {f(n)/f(n-1)} for positive integers n-s covers all the positive rational numbers in reduced form.
If n is odd (=2m+1), from the definition of f(n) (modulo 2) we get that 1 (=2^0) appears exactly once and hence
(1a) f(2m+1) = f(m).
If n is even (=2m), 1 either does not appear at all or appears twice. In the first case, we get f(m) possibilities and in the second we get f(m-1). Therefore,
(1b) f(2m)=f(m)+f(m-1).
Clearly f(n)>0 and therefore
(2) f(2n-1) = f(n-1) < f(n-1)+f(n) = f(2n).
Claim 1: gcd(f(n),f(n-1))=1
Proof: By induction on n. The base (n=1) is trivial: gcd(f(1),f(0))=gcd(1,1)=1
Suppose the induction hypothesis holds for k<n, then from (1a) & (1b):
gcd(f(n),f(n-1)) = gcd(f(2m+1),f(2m)) = gcd(f(m), f(m)+f(m-1)) = gcd(f(m),f(m-1)) = 1
or
gcd(f(n),f(n-1)) = gcd(f(2m),f(2m-1)) = gcd(f(m)+f(m-1), f(m-1)) = gcd(f(m),f(m-1)) = 1
qed.
Claim 2: f(n+1)/f(n) = f(n’+1)/f(n’) implies that n=n’
Proof: Again, by induction on max(n,n’). The base (max(n,n’)=0) is trivial since n=n’=0.
Assume the induction hypothesis holds for k<n, then from (2) we get that
f(n)/f(n-1) = f(n’)/f(n’-1) can only hold when n=n’(mod 2) and from (1a)&(1b) we get
f(m)/f(m-1) = f(m’)/f(m’-1) and by induction m=m’ yields n=n’.
qed.
Claim 3: For every positive rational number r, there exists a positive integer n such that r = f(n)/f(n-1).
Proof: Write r as a quotient of two relative prime natural numbers p and q.
We prove by induction on max(p,q).
The base (p=q=1) is trivial: n=1.
Assume the induction hypothesis holds for all k<n.
If p<q (q<p), then define r’ as p’/q’ where p’=p & q’=q-p (p’=q & q’=p-q). r’ satisfies the induction hypothesis and therefore r’ = f(m)/f(m-1). Hence r = f(2m+1)/f(2m) (f(2m)/f(2m-1))
qed.
If you have any problems you think we might enjoy, please send them in. All replies should be sent to: ponder@il.ibm.com